2014
DOI: 10.1007/s11605-014-2496-2
|View full text |Cite
|
Sign up to set email alerts
|

Peroral Endoscopic Myotomy (POEM): Feasible as Reoperation Following Heller Myotomy

Abstract: POEM is a feasible option for patients after failed myotomy even in the presence of prior fundoplication. The procedure can be performed safely using a similar technique as for primary myotomy with the exception of creating the myotomy laterally along the right side of the esophagus and lesser curvature avoiding the previous anterior myotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 15 publications
0
58
0
Order By: Relevance
“…POEM has even been performed successfully on refractory cases of achalasia following previous balloon dilation or laparoscopic Heller myotomy [52][53][54][55]. These cases should only be treated by highly experienced operators [47].…”
Section: Treatmentmentioning
confidence: 99%
“…POEM has even been performed successfully on refractory cases of achalasia following previous balloon dilation or laparoscopic Heller myotomy [52][53][54][55]. These cases should only be treated by highly experienced operators [47].…”
Section: Treatmentmentioning
confidence: 99%
“…required a median 7 (4-16) and 8 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) clips, respectively (p = 0.08). Length of stay was 1 day in each group.…”
mentioning
confidence: 99%
“…In addition, it has been shown that POEM is a feasible option for patients after a failed myotomy even in the presence of a fundoplication. Post-operative changes are not evident in these patients and the mean operating time is not affected by a previous myotomy [ 12 ]. Compared to LHM, which is currently viewed as the gold standard, POEM patients experience less pain, take fewer narcotics, and have a quicker return to activities of daily living (ADL) [ 13 ].…”
Section: Discussionmentioning
confidence: 97%